NEW EARLY TUVALIAN (CARNIAN, TRIASSIC) RADIOLARIANS FROM THE HUǦLU-PINDOS SUCCESSION IN THE SORGUN OPHIOLITIC MÉLANGE, SOUTHERN TURKEY - Ozsvárt, Péter; Dumitrica, Paulian; Moix, Patrice (Ofioliti, 2017)
Three new radiolarian genera (Paramonocapnuchosphaera, Monocoronella and Minicrampus) and 8 new species are described herein from one of the most diverse and best preserved Carnian (Late Triassic) radiolarian faunas of the world, from the early Tuvalian sequence of the Sorgun Ophiolitic Mélange, southern Turkey. The radiolarian fauna belongs to the Spongotortilispinus moixi Zone (equivalent to Paragondolella postinclinata - Paragondolella noah conodont Zone). The very similar late Julian-early Tuvalian radiolarian faunas from the Northern Calcareous, Alps through the Lagonegro Basin, Sicily, Rhodes Island, Greece and farther east in the Antalya nappes, in the Mersin Mélange and in Elbistan, Turkey may confirm that the Pindos-type succession found in different units of early Mesozoic oceanic basins formed in a single oceanic basin.